Coxsackievirus B4 vertical transmission in a murine model. Issue 1 (December 2017) - Jaïdane, Hela; Halouani, Aymen; Jmii, Habib; Elmastour, Firas; Mokni, Moncef; Aouni, Mahjoub
Abstract Background Life-threatening infections with type B Coxsackieviruses (CV-B) are frequently encountered among newborns and are partly attributed to vertically-transmitted virus. Our current study investigates this alternative way of contamination by CV-B, using a mouse model. Methods PregnantSwiss mice were intraperitoneally inoculated with CV-B4 E2 at gestational day 10(G) or 17G. Dams and offspring were monitored for mortality and morbidity, and sampled at different time-points to document the infection and explore eventual vertical transmission. Results Inoculation at day 10G induced an important rate of abortion and a decrease in the number of delivered pups per litter, whereas inoculation at day 17G was marked by preterm delivery and significant behavioral changes in dams. Only one case of spastic paralysis and one case of pancreatitis were recorded among surviving pups. Seroneutralization revealed anti-CV-B4 neutralizing antibodies in infected dams and their partial transfer to offspring. Viral genome detection by RT-PCR and viral progeny titration in several tissues (dams' uteri, amniotic sac, amniotic fluid, placenta, umbilical cord, pancreas and heart) attested and documented CV-B4 vertical transmission to the majority of analyzed offspring. Virus detection in fetuses suggests transplacental transmission, but perinatal transmission during delivery could be also suggested. Vertically transmitted CV-B might even persist since prolonged viral RNA detection was noticed in the pancreas and heart from offspring born to dams inoculated at day 17G. Conclusion This model of CV-B4 vertical transmission in mice, in addition to allow a better understanding of CV-B infections in fetuses and newborns, constitutes a useful tool to investigate the pathogenesis of CV-B associated chronic diseases.